Deficiency in Calcium-Binding Protein S100A4 Impairs the Adjuvant Action of Cholera Toxin - Sun, Jia-Bin; Holmgren, Jan; Larena, Maximilian; Terrinoni, Manuela; Fang, Yu; Bresnick, Anne R.; Xiang, Zou (Frontiers in Immunology, 2017)
The calcium-binding protein S100A4 has been described to promote pathological inflammation in experimental autoimmune and inflammatory disorders and in allergy and to contribute to antigen presentation and antibody response after parenteral immunization with an alum-adjuvanted antigen. In this study, we extend these findings by demonstrating that mice lacking S100A4 have a defective humoral as well as cellular immune response to mucosal (sublingual) immunization with a model protein antigen (ovalbumin, OVA) given together with the strong mucosal adjuvant cholera toxin (CT), and that this impairment is due to defective adjuvant-stimulated antigen presentation by antigen presenting cells. In comparison to wild-type (WT) mice, mice genetically lacking S100A4 had reduced humoral and cellular immune responses after immunization with OVA plus CT, including a complete lack of detectable germinal center reaction. Further, when stimulated in vitro with OVA plus CT, S100A4-/- dendritic cells (DCs) showed impaired responses in several CT-stimulated immune regulatory molecules including the costimulatory molecule CD86 and inflammasome-associated IL-1β. Co-culture of OVA-specific OT-II T cells with S100A4-/- DCs that had been pulse-incubated with OVA plus CT resulted in impaired OT-II T cell proliferation and reduced production of Th1, Th2 and Th17 cytokines compared to similar co-cultures with WT DCs. In accordance with these findings, transfection of WT DCs with S100A4-targeting silencing RNA (siRNA) but not mock-siRNA resulted in significant reductions in the expression of caspase-1 and IL-1 as well as CD86 in response to CT. Importantly also, engraftment of WT DCs into S100A4-/- mice effectively restored the immune response to immunization in the recipients. In conclusion, our results demonstrate that deficiency in S100A4 has a strong impact on the development of both humoral and cellular immunity after mucosal immunization using CT as adjuvant.